Handheld computing in pathology - Seung Park; Anil Parwani; Mahadev Satyanarayanan; Liron Pantanowitz (Elsevier, 2012)
Handheld computing has had many applications in medicine, but relatively few in pathology. Most reported uses of handhelds in pathology have been limited to experimental endeavors in telemedicine or education. With recent advances in handheld hardware and software, along with concurrent advances in whole-slide imaging (WSI), new opportunities and challenges have presented themselves. This review addresses the current state of handheld hardware and software, provides a history of handheld devices in medicine focusing on pathology, and presents future use cases for such handhelds in pathology.